Parasite species richness and intensity of interspecific interactions increase with latitude in two wide‐ranging hosts. Issue 11 (1st November 2015) - Torchin, Mark E.; Miura, Osamu; Hechinger, Ryan F.
Abstract : Although the latitudinal diversity gradient is a well‐known and general pattern, the mechanisms structuring it remain elusive. Two key issues limit differentiating these. First, habitat type usually varies with latitude, precluding a standardized evaluation of species richness. Second, broad‐scale and local factors hypothesized to shape diversity patterns co‐vary with one another, making it difficult to tease apart independent effects. Examining communities of parasites in widely distributed hosts can eliminate some of these confounding factors. We quantified diversity and interspecific interactions for trematode parasites infecting two similar snail species across 27 degrees of latitude from 43 locations in tropical and temperate oceans. Counter to typical patterns, we found that species richness, levels of parasitism, and intensity of intraguild predation increased with latitude. Because speciation rates are precluded from driving diversity gradients in this particular system, the reversed gradients are likely due to local ecological factors, specifically, increased productivity and stability. We highlight how this system may serve as a useful tool to provide insight into what processes drive diversity gradients in general.